2020
DOI: 10.3389/fpsyg.2020.00129
|View full text |Cite
|
Sign up to set email alerts
|

Why Do People With Self-Control Forgive Others Easily? The Role of Rumination and Anger

Abstract: Previous research shows that self-control predicts forgiveness, but few studies have investigated the internal mechanism of this link. The current study explored the effects of rumination and anger on the relationship between self-control and forgiveness. A total of 580 college students recruited from three universities in Wuhan completed the self-control, rumination, anger, and trait forgiveness scales. Results showed that self-control was positively correlated with forgiveness (r = 0.34, p < 0.001). Ruminati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Influenced by the Confucian Golden Mean philosophy, the Chinese may value social harmony much more than Westerners ( Drummond and Quah, 2001 ; de Greck et al, 2012 ; Liu, 2014 ). In light of Chinese culture, expressing anger could be labeled as lacking in self-control ( Kornacki, 2001 ; Kong et al, 2020 ). In contrast, for Westerners, sincerely expressing emotions could be deemed as a way to enhance interpersonal understanding ( Gross and John, 2003 ; Murata et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Influenced by the Confucian Golden Mean philosophy, the Chinese may value social harmony much more than Westerners ( Drummond and Quah, 2001 ; de Greck et al, 2012 ; Liu, 2014 ). In light of Chinese culture, expressing anger could be labeled as lacking in self-control ( Kornacki, 2001 ; Kong et al, 2020 ). In contrast, for Westerners, sincerely expressing emotions could be deemed as a way to enhance interpersonal understanding ( Gross and John, 2003 ; Murata et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Further work to explore potential mechanisms is also needed. Recent studies, mostly cross-sectional, have suggested that rumination, anger [41], empathy [42], selfregulation [43], and emotional regulation [11] as possible mechanisms of forgiveness. Further studies on such mechanisms with longitudinal data and formal mediation analyses would be warranted.…”
Section: Forgiveness Mental Health and Psychosocial Well-beingmentioning
confidence: 99%
“…Recent research suggests that reducing rumination may facilitate forgiveness [ 37 ]. Forgiveness explained a significant amount of variation in ARS (anger rumination) scores, even when the thoughts of revenge subscale was removed.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research suggests that reducing rumination may facilitate the cognitive decision to forgive [ 37 ], that rumination negatively predicts forgiveness, and that the possibility of forgiveness can be increased by reducing rumination [ 38 , 39 , 40 ]. These results have also been found in cross-cultural research [ 41 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation